Demanda por saneamento básico no Brasil: uma análise com uso do modelo multinomial logit - Mendonça, Mário Jorge Cardoso de; Sachsida, Adolfo; Loureiro, Paulo Roberto Amorim (Economia Aplicada, 2004)
Basic sanitary services, that include waste disposal, treated water supplies and sewage services, have a strong effect on human health and on the environment. Brazil stands as having a large deficit in these services which results in a decrease in the productivity of labor and losses in GDP. This study aims at estimating an exploratory sanitary service demand model for Brazil. Two complementary approaches are used. The first one is a demand model estimated by a logit type regression where the three sanitary services are jointly analyzed. The second model takes each component individually for analytical purposes. In this sense, a random utility model based on the multinomial logit is used for waste disposal and sewage. In spite of data limitation, in both models it was possible to observe that demand is sensitive to factors such as education, family background, race, location, etc. Also relevant as a determining factor is the effect of household income, being especially true for poorer households.